Clinical recurrence of submucosal myoma after a mechanical hysteroscopic myomectomy: Review after 5 years follow up. (December 2019) - Vidal-Mazo, Cinta; Forero-Diaz, Carmen; Lopez-Gonzalez, Elga; Yera-Gilabert, Marta; Machancoses, Francisco H.
Abstract: Objective: Evaluation of five years follow up of the clinical recurrence after hysteroscopic myomectomies with MyoSure® morcellator in our district. Study design: Premenopausal patients from April 2013 to October 2018, with symptoms of abnormal uterine bleeding, and/or infertility, and sonographic suspicion of submucosal myoma, confirmed by diagnostic hysteroscopy prior to myomectomy were included in the prospective, not randomized cohort study (N = 320). All patients had a follow up visit between three to six months post procedure. Further follow up was established by chart review. The information was extracted from the medical records. Patient characteristics were expressed as mean ± SD or median (interquartile range) for continuous data (assumption of normality assessed using the Kolmogorov-Smirnov test). Dependence relationship between presence of corporal myomas and the performance of a major long-term surgery, and between the amount of submucosal myomas and clinical recurrence throughout the 5 years of follow-up were studied were studied by χ 2 . Results: After one year follow up, no recurrence or symptoms were noted. 53 (16.6%) re-morcellations were performed due to incomplete resection. At the second year, three women who were discharged previously were classified as recurrence (0.9%). There were 99 women remaining to be evaluated (30.90%) in the second year. A percentage estimation of 5–6 recurrences with the 100% of women evaluated. In the third year, only one woman was classified as recurrence (0.3%), with 176 (55%) women not evaluated. At the fourth and fifth year of follow-up, 75% are still awaiting complete of the study five years. No relationship was observed in the presence of corporal myomas and recurrence throughout the 5 years of follow-up (χ 2 = 0.000, p = 0.994). Dependence relationship was observed between the presence of corporal myomas and the performance of a major long-term surgery (χ 2 = 11.757, p = .001, OR = 3.528). Conclusion: In office hysteroscopic mechanical myomectomy with MyoSure® morcellator of submucosal fibromas was a highly effective therapy for women, at three years of follow-up. It appears to give satisfactory long-term results with a low recurrence rate and without significant complications.